Transmit space-frequency prefiltering technique for downlink TDD MC-CDMA systems - Silva, Adão
In this communication we present a space-frequency pre-filtering technique, for downlink time division duplex (TDD) MC-CDMA systems, where the base station is equipped with an antenna array. We show that the pre-filtering approach can considerably reduce the multiple access interference at the mobile terminals allowing to transfer a significant part of the computational complexity to the base station, using a very low complex receiver at mobile. This approach relies on the availability of the channel state information at transmission, i.e., uses the time division duplex channel reciprocity between alternative uplink and downlink to obtain the channel state information. Simulation results are presented to demonstrate the effectiveness of the proposed prefiltering algorithm. Moreover, the performance of the proposed pre-filtering algorithm is assessed in two distinct scenarios: beamforming and diversity.